Modified Variant of Correction of Abnormal Pulmonary Vein Drainage (Eurasian Medical Research Periodical, 2023)
During the period from 2015-2021 we operated on 51 patients aged 5 - 45 years. Vahidov RSNPCh operated 51 patients aged 5 - 45 years, with different anatomical variants of anomalous pulmonary vein drainage (ADLV). The diagnosis of malformation was based on the analysis of the combined data of clinical and special research methods, including echocardiography, multispiral computed tomography with contrast and cardiac cavity catheterization with angiocardiography. The surgeries were performed from median sternotomy, under artificial circulation with pharmaco-cold cardioplegia. The types of surgery in supracardiac type of partial anomalous pulmonary vein drainage are analyzed. The modified variant of supracardial type ADLV correction is outlined; the results of the operation are compared with the classical methods of operation